2017
DOI: 10.4236/jbm.2017.512011
|View full text |Cite
|
Sign up to set email alerts
|

Folic Acid Supplementation Ameliorates Inflammation and Apoptosis in Ethanol-Induced Gastric Ulceration in Rats

Abstract: Although the gastroprotective potential of folic acid has been reported, little is known about the role of inflammation and apoptosis in the said activity. This study, therefore, assessed lipid peroxidation (LPO), Neutrophil-lymphocyte ratio (NLR), C-reactive protein (CRP) as markers of inflammation and, p53 and BCl-2 as markers of apoptosis in ethanol-induced gastric ulcer pretreated with Folic acid (FA) for twenty-one (21) days. Adult male Wistar rats were arranged into experimental groups (n = 5) viz: 1) Co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 40 publications
0
2
0
Order By: Relevance
“…A recent study demonstrated that folate supplementation enhanced the expression of angiogenesis-related factors such as EGF and VEGF, increased the expression of Ki-67 related to cell proliferation, and reduced the severity of ulcers in mice with GU [21]. In addition, folate can protect gastric mucosa from ethanolinduced acute damage through anti-in ammatory and anti-apoptotic mechanisms [20]. However, it should be noted that high-dose folate may damage the integrity of gastric mucosa, as suggested by some studies [19].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A recent study demonstrated that folate supplementation enhanced the expression of angiogenesis-related factors such as EGF and VEGF, increased the expression of Ki-67 related to cell proliferation, and reduced the severity of ulcers in mice with GU [21]. In addition, folate can protect gastric mucosa from ethanolinduced acute damage through anti-in ammatory and anti-apoptotic mechanisms [20]. However, it should be noted that high-dose folate may damage the integrity of gastric mucosa, as suggested by some studies [19].…”
Section: Discussionmentioning
confidence: 99%
“…However, the potential impact of folic acid on gastric mucosa has received little attention. Several studies have demonstrated that pretreatment with folic acid can effectively prevent the formation of gastric ulcers [17][18][19][20][21]. Nevertheless, most of these studies have been limited to the animal and cellular level and lack of clinical and genetic evidence, which limits their reliability.…”
Section: Introductionmentioning
confidence: 99%